PAME MPA-network toolbox (2015-2017); Area-based conservation measures and ecological connectivitiy - Protection of the Arctic Marine Environment (PAME) (Protection of the Arctic Marine Environment, 2017)
PAME's "Toolbox" project aims to develop guidance to assist Arctic States in advancing their MPA networks by providing theory and tools that can be used to assess and protect the diversity of genes, species, populations, habitats, features, and ecosystems; their interaction; and the ability to adapt to change. PAME's Framework for a Pan-Arctic Network of Marine protected Areas (Arctic Council 2015) offers a foundation of goals and objectives on which this toolbox builds.